2004
DOI: 10.1007/978-3-540-24855-2_121
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Human-Competitive Image Texture Feature Extraction Programs Using Genetic Programming

Abstract: Abstract. In this paper we show how genetic programming can be used to discover useful texture feature extraction algorithms. Grey level histograms of different textures are used as inputs to the evolved programs. One dimensional K-means clustering is applied to the outputs and the tightness of the clusters is used as the fitness measure. To test generality, textures from the Brodatz library were used in learning phase and the evolved features were used on classification problems based on the Vistex library. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…It incorporates implementation of Fourier and wavelet transforms, along with a covariance matrix and statistical momentum as features. (Further relevant details can be found in [22], [6], [17], [1], [3], [23], [5], [7], [10], [12], [31], [24], [19]. )…”
Section: A Past Workmentioning
confidence: 99%
“…It incorporates implementation of Fourier and wavelet transforms, along with a covariance matrix and statistical momentum as features. (Further relevant details can be found in [22], [6], [17], [1], [3], [23], [5], [7], [10], [12], [31], [24], [19]. )…”
Section: A Past Workmentioning
confidence: 99%
“…Aurnhammer [23] and Lam et al [24] described the use of genetic programming to generate texture features and reported very promising results on image classification problems. Li et al [25] proposed a hybrid of a co-evolutionary genetic programming and expectation maximisation algorithm applied on partially labelled data.…”
Section: Evolutionary Feature Synthesismentioning
confidence: 99%
“…features to evolve the classification rules [7]. Inspired by the psycho visual study, multi-scale processing Keywords -Classification, Genetic Programming, Texture is a promising way to deal with texture analysis.…”
mentioning
confidence: 99%